Effect of foliar spray selenium on antioxidant defense system, yields, fatty acid composition, and mineral concentrations in flax (Linum usitatissimum L.) - Xie, Yaping; Zhou, Yangchen; Wang, Limin; Li, Wenjuan; Zhao, Wei; Dang, Zhao; Wang, Xingzhen; Duan, Yanqiao; Zhang, Jianping; Yuan, Minlu; Wang, Gang (Frontiers in Plant Science, 2025)
IntroductionFlax is an important multipurpose oil crop with high-quality seed, oil, and fibre. MethodsThis study aims to investigate the effect of selenium (Se) fertilization on the flax antioxidant defense system, yields, fatty acid composition, and mineral concentrations. A field experiment was conducted in Gansu, Northwest China in 2022, 2023, and 2024, by foliar application of Se at early budding, early flowering, and early seed-filling using a low-pressure hand sprayer. A randomized complete block design with three replicates was employed by analyzing physiological and biochemical characteristics to assess yield and quality of flax.ResultsResult showed that harvest year significantly influenced proline, soluble sugar, oil, oleic, linoleic and linolenic acid contents, the superoxide dismutase activity in leaves, lignans, Se, calcium, and iron concentrations in seeds, the number of capsules per plant, and the yields of seed, lignans, oil, and oil cake. The proline and soluble sugar contents, superoxide dismutase, peroxidase, and catalase activities and number of capsules per plant, Se, zinc, and iron concentrations, as well as seed, oil, lignans, and flaxseed oil cake yields increased by foliar Se, while reducing malondialdehyde and cadmium levels, compared to without Se application. Specifically, the highest number of capsules per plant was observed at Se of 30 mg L–1; the yields of seed, oil, lignans, and flaxseed oil cake were achieved at Se of 40 mg L–1, however, there was no significant difference in foliar Se between 30 and 40 mg L–1 across harvests. Moreover, the iron and zinc concentrations reached the peaked at Se of 20 mg L–1, and Se concentration was measured at 50 mg L–1. In conclusion, foliar application of appropriate Se is an effective agronomic management approach to enhance yields and quality of flax by enhancing the antioxidant defense as well as promoting absorption and accumulation of Se, iron, and zinc in seeds.DiscussionFuture experiments will systematically investigate the effects of Se type, foliar spray timing, and application frequency on the nutrient content, hormone levels, stress resistance, yield, and quality of flax.